WITS A History of the University of the Witwatersrand, Johannesburg, and Its Precursors 1896-1939. - Murray, Bruce (Wits Press re/presents., 2022)
Examining the historical foundations, the struggle to establish a university in Johannesburg, and the progress of the University in the two decades prior to World War II, historian Bruce Murray captures the quality and texture of life in the early years of Wits University and the personalities who enlivened it and contributed to its growth.